Buddhism and Ethnic Conflict in Sri Lanka, by Patrick Grant. - Harris, Elizabeth J. (Buddhist Studies Review, 2009)
Buddhism and Ethnic Conflict in Sri Lanka, by Patrick Grant. Albany: State University of New York Press, 2009. 146 + xiv pp., (HB) 60.00, ISBN-13: 978-0791493533.